P173 The grenfell fire: experience of a community clinic. (12th November 2019) - Stone, B; Owles, HLB; Wong, E; Mallia, P; Ghafur, S; Mak, V; Wickremasinghe, M; Elkin, SL
Abstract : Introduction: The Grenfell Tower fire in 2017 claimed 72 lives and hospitalised a further 74. Following this disaster a rapid access respiratory outpatient service was offered to all primary care patients affected by the fire. We aim to identify the symptoms leading to referrals and any new diagnoses made. Methods: The patient records were reviewed for all those referred to the rapid access respiratory clinic between 14/07/2017 and 1/7/2019. Data was collected on demographics, smoking status, co-morbidities, reason for referral, respiratory diagnosis and ongoing management. Results: 77 patients were referred. 21/77 (27%) lived in Grenfell Tower on the night of the fire, the others were from the surrounding area. 8/77 (10%) had been admitted on the night of the fire. Patients were 18–83 years (median 50 years) with a slight female (61%) predominance. 46/77 (60%) had a smoking history. The main symptoms resulting in referral were cough (64%), dyspnoea (39%) and wheeze (19%). Of the patients referred, 13/77 (17%) did not attend their appointment and 5/77 (6%) currently are awaiting a first appointment. Of the 59 patients reviewed, all patients were offered spirometry and 44/59 (75%) had thoracic imaging (CT or chest radiograph). Respiratory physicians had access to further tests from clinic including: lung volumes, gas transfer, bronchodilator reversibility, exhaled nitric oxide, histamine challenges and echocardiograms. 12/59 (20%) patients had pre-existing respiratory conditions confirmed. A further 12/59 were diagnosed with a new chronic respiratory disease: 6 asthma, 3 COPD, 2 ILD, 1 bronchiectasis. Of these 6/12 (50%) had respiratory symptoms pre-dating but exacerbated by the fire. 7/59 (12%) had temporary symptoms due to smoke/dust inhalation which either self-resolved or improved with inhaled corticosteroids. There was overlap between respiratory symptoms and anxiety after the fire. 7/59 (12%) patients were referred to dyspnoea clinic for breathing pattern disorders, meanwhile 35/59 (59%) patients received simultaneous support from the mental health team. Conclusion: The Grenfell Fire resulted in a local increase in respiratory symptoms and an increase in new respiratory diagnosis. A rapid access respiratory service helped optimise pre-existing respiratory conditions and identify patients with previously undiagnosed respiratory disease exacerbated by the fire.